Meningkatkan Motivasi, Aktivitas, dan Hasil Belajar IPS Menggunakan Model BATIK pada Siswa Kelas V SDN Manarap Lama 1 - Dewi Nugraheni; Raihanah Sari (CV. ITTC INDONESIA, 2023)
The problem in this study is the low motivation, activity and student learning outcomes in social studies learning. This study aims to analyze motivation, activity, and improvement of student learning outcomes. This research was carried out using a qualitative and quantitative approach with the type of Classroom Action Research (CAR) which was held in 4 meetings in the VA class of SDN Manarap Lama 1 in the academic year 2022/2023 with a total of 27 students. The research instrument used observation sheets of teacher activity, observation of student activity, student learning motivation questionnaires and student learning outcomes. Then analyzed with descriptive techniques and described in the form of tables and graphs. The results showed that teacher activity increased and reached a percentage of 96.87% with the criteria